2016
DOI: 10.18632/oncotarget.13305
|View full text |Cite
|
Sign up to set email alerts
|

Interim analysis of a phase I/IIa trial assessing E39+GM-CSF, a folate binding protein vaccine, to prevent recurrence in ovarian and endometrial cancer patients

Abstract: BACKGROUNDFolate binding protein(FBP) is an immunogenic protein over-expressed in endometrial(EC) and ovarian cancer(OC). We are conducting a phase I/IIa trial of E39 (GALE 301)+GM-CSF, an HLA-A2-restricted, FBP-derived peptide vaccine to prevent recurrences in disease-free EC and OC patients. This interim analysis summarizes toxicity, immunologic responses, and clinical outcomes to date.METHODSHLA-A2+ patients were vaccinated(VG), and HLA-A2- or -A2+ patients were followed as controls(CG). Six monthly intrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…While the E39 peptide was previously shown to be safe and well-tolerated in a trial enrolling patients with ovarian and endometrial cancer, the safety of E39′ inoculations in humans has not been previously demonstrated [10]. In this study, patients receiving E39′ as a component of their PVS experienced only grade 1 and 2 toxicities confirming the safety of this attenuated peptide.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…While the E39 peptide was previously shown to be safe and well-tolerated in a trial enrolling patients with ovarian and endometrial cancer, the safety of E39′ inoculations in humans has not been previously demonstrated [10]. In this study, patients receiving E39′ as a component of their PVS experienced only grade 1 and 2 toxicities confirming the safety of this attenuated peptide.…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, the indication from these DTH results, that a lower dose of peptide induces a more meaningful immune response, is in contrast with our recently published results from the phase I/IIb trial of the E39 peptide vaccine in patients with endometrial and ovarian cancer where patients receiving a higher vaccine dose demonstrated better clinical outcome [10]. This difference may be related to the differences in patient populations.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations